Marker Spesifik Combine DNA Index System (CODIS) 13 dalam Identifikasi Forensik pada Suku Jawa dan Madura di Indonesia - Wening Prastowo; Fitria Dewi Listiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2014)
Forensic identification can be performed DNA examination. FBI had recommended, forensic DNA examination to used short tandem repeat CODIS 13. Result of determine Short tandem repeat CODIS 13, showed specific pattern. Java tribes are shown, the Heterozygousity Index ranged from 0,60069 (VWA) to 0.93752 (D18S51), the Power of Exclution ranged from 0.30885 (VWA), to 0.83068 (D18S51), the Power of Discrimination ranged from 0.52853 (VWA), to 0.99127 (D18S51). Madura tribes shown, the Heterozygousity Index ranged from 0,63021 (VWA) to 0.94445 (FGA), the Power of Exclution ranged from 0.33418 (VWA), to 0.84779 (FGA), the Power of Discrimination ranged from 0.60501 (TPOX), to 0.99305 ( FGA).